Implementasi Kebijakan Penanggulangan Stunting di Puskesmas Pangkalan Balai Kabupaten Banyuasin - Yusdiana Yusdiana; Ririn Noviyanti Putri; Rina SE Sitindaon (Universitas Batanghari Jambi, 2023)
The problem of stunting in Indonesia is a serious threat that requires proper handling. Toddlers who are stunted have a risk of intellectual decline, productivity and an increased risk of degenerative diseases in the future. One of the policies made by the Palembang City Government related to tackling stunting incidents, namely through Banyuasin Regent Regulation Number 49 of 2018 concerning accelerating stunting prevention, controlling and reducing integrated stunting. The purpose of this study was to analyze government policies related to stunting prevention in the city of Palembang. The results of the study are that the implementation of the stunting reduction policy has been carried out properly in accordance with Banyuasin Regent Regulation Number 49 of 2018 and the Rembuk Stunting Program by the Banyuasin District Health Office in collaboration with all Banyuasin District Health Centers in order to Accelerate Stunting Reduction in Banyuasin District, the clarity of the stunting prevention policy at the Pangkalan Balai Health Center has been socialized to health workers, the staff in supporting the stunting prevention program at the Pangkalan Balai Health Center is sufficient, the facilities available to run the stunting prevention program at the Pangkalan Balai Health Center is appropriate and appropriate, coordination for the formation of Pangkalan Balai Health Center commitments through cross-sectors, SOPs for the implementation of the stunting policy are available. The results of this study are expected to be an illustration for the puskesmas to be able to further improve stunting services.Â